Health care costs of Attention Deficit Hyperactivity Disorder - Lucas, Nina; Gold, Lisa; Sciberras, Emma; Hiscock, Harriet; Efron, Daryl; Nicholson, Jan (My University, 2011)
Aims: Attention-Deficit/Hyperactivity Disorder (ADHD) is highly prevalent, affecting approximately 7% of Australian school-aged children. Children with ADHD are more likely than their peers to experience both comorbid internalizing and externalizing difficulties. This study aims to investigate: 1) the health care costs associated with ADHD in early childhood; and 2) the impact of comorbid internalizing and externalizing difficulties on the health care costs associated with ADHD. Methods: Data from LSAC (B and K cohorts) will be used to estimate the Medicare costs associated with ADHD from birth to 8 years. ADHD will be defined by parent-reported diagnosed ADHD (aged 4-8 years) and/or clinically elevated Inattention-Hyperactivity scores on the parent-reported Strengths and Difficulties Questionnaire (SDQ) (aged 4-8 years). Internalising and externalising comorbidities will be defined by clinically elevated scores on the Emotional Problems and Conduct Problems subscales of the SDQ. Results: We will report average health care costs (PBS, MBS and combined costs separately) for children with and without ADHD and will estimate costs at the population level for children with and without ADHD. The average number of health care visits and PBS prescriptions for children with and without ADHD will be reported. Furthermore, we will report average health care costs for children with ADHD and internalizing/externalsing comorbidities versus children with ADHD alone. Conclusion: This study will provide the first Australian data reporting on the health care costs associated with ADHD and its common comorbidities. We expect that ADHD will be associated with considerable health care costs.
Keywords: Health -- Access to services; Child Development; Child Development -- Behaviour; Income & Finance -- Expenditure and constraints on expenditure; Childhood and child development; Health and wellbeing; Income, wealth and finances; Health; Income & Finance; Child Development; Access to services; Behaviour; Expenditure and constraints on expenditure; Income, wealth and finances; Health and wellbeing; Childhood and child development